0324 2B-Alert Web 2.0: An Open-access Tool to Determine Caffeine Doses That Optimize Alertness. (12th April 2019) - Kumar, Kamal; Vital-Lopez, Francisco; Ramakrishnan, Sridhar; Doty, Tracy J; Balkin, Thomas J; Reifman, Jaques
Abstract: Introduction: Caffeine is the most widely consumed stimulant to counter the effects of sleep deprivation on alertness. However, to be safe and most effective, the right amount must be consumed at the right time. Recently, we developed an algorithm that automatically provides guidance for optimal caffeine consumption to safely maximize alertness at the desired time of the day. However, to be useful to the research and schedule-planner communities, we made this capability freely available through a Web server, where users can compare and contrast the effects of different sleep/wake and caffeine schedules on alertness. Methods: We extended our previously developed open-access Web tool, 2B-Alert Web, by incorporating the automated caffeine-guidance algorithm. Specifically, in this version, we allow users to input 1) desirable peak-alertness periods within a sleep/wake schedule, 2) the minimum desirable level of alertness, and 3) the maximum tolerable daily caffeine intake (≤ 1500 mg). The tool then provides the optimal caffeine doses (timing and amount) to achieve peak alertness levels at the desired times, while meeting user-defined constraints. It also displays the corresponding psychomotor vigilance test alertness predictions, which together with the caffeine guidance, can be exported to a spreadsheet. Results: When we compared the 2B-Alert Web 2.0 caffeine-consumption guidance for multiple sleep-deprivation and shift-work scenarios with the U.S. Army guidelines, we observed an average improvement of 40%. The tool suggested solutions that either required 40% less caffeine or that enhanced alertness by an additional 40%. Conclusion: With this added capability, the 2B-Alert Web 2.0 now allows users to 1) predict the alertness of an "average" individual as a function of sleep/wake and caffeine schedules and 2) automatically obtain optimal caffeine doses (timing and amount) to achieve peak alertness at the desired times. As such, it provides the first quantitative caffeine optimization tool for designing effective strategies to maximize alertness, while avoiding excessive caffeine consumption. Support (If Any): This work was sponsored by the Military Operational Medicine Program Area Directorate of the U.S. Army Medical Research and Materiel Command, Ft. Detrick, MD.